Intelligent Recognition System Based on Contour Accentuation for Navigation Marks. (3rd March 2021) - Du, Yanke; Sun, Shuo; Qiu, Shi; Li, Shaoxi; Pan, Mingyang; Chen, Chi-Hua
Abstract : Sensing navigational environment represented by navigation marks is an important task for unmanned ships and intelligent navigation systems, and the sensing can be performed by recognizing the images from a camera. In order to improve the image recognition accuracy, this paper combined a contour accentuation algorithm into a multiple scale attention mechanism-based classification model for navigation marks. Experimental results show that the method increases the accuracy of navigation mark classification from 95.98% to 96.53%. Based on the classification model, an intelligent navigation mark recognition system was developed for the Changjiang Nanjing Waterway Bureau, in which the model is deployed and updated by the TensorFlow Serving.